Increasing public managers’ perceived autonomy by decreasing the level of detail in payment models? The dependency and interdependency of control practices - Glenngård, Anna; Ellegård, Lina Maria (Financial Accountability & Management, 2025)
We investigate public managers' perceptions about the characteristics of global budgets and the association with perceived autonomy, using a qualitative, experiential approach. We compare and contrast differences in managers perceived autonomy associated with the use of global budgets in two large public healthcare organizations, while considering both the characteristics of other control practices and their dependencies and interdependencies with the payment model. The results from our comparative case-study support and nuance the finding in previous research that perceptions about payment models depend on how they are combined with other controls, by illustrating that such perceptions depend on how payment models are integrated into a MCS. Our comparative study nuances the picture from previous research about the interplay between formalization, uncertainty, room for maneuver, and perceived autonomy. Our empirical findings illustrate that room for maneuver is positively associated with perceived autonomy only if control practices are combined such that managers also experience a low level of uncertainty about outcome goals and how to perform their job. Role clarity and room for maneuver are interdependent in relation to perceived autonomy via enabling effects. The results suggest that control extensiveness is not perceived in a negative way if controls offer flexibility and contribute to knowledge and mutual understanding about priorities and organizational goals.